Deep long period volcanic earthquakes generated by degassing of volatile-rich basaltic magmas - Oleg Melnik (Nature Portfolio, 2020)
The origin of deep long-period earthquakes beneath active volcanoes that are sometimes considered as precursors to eruptions remains not fully understood. Here the authors show that these earthquakes can be generated by the rapid degassing in response to the slow decompression of magma over-saturated with H2O and CO2.